Monitoring Status Gangguan Listrik Pada Saluran Distribusi Berbasis Arduino - Dino Dwi Putra; Oriza Candra (JTEV (Jurnal Teknik Elektro dan Vokasional), 2021)
Abstract  power is a source of strength that has a very critical role in normal existence, beginning from domestic affairs, workplaces, and so forth. If the electricity is cut off or dead, a lot of work using these electronic devices will be neglected. If a power cut occurs due to a disruption in the distribution line, the public can provide an information report in the form of a telephone call or visit the PLN office to report to the operator if in their area the electricity has problems. However, unlike people in areas such as rural areas, there is very little attention to this kind of information and it is difficult for operators to monitor distribution channels in the area. Therefore, it is necessary to make a monitoring tool for the status of electrical disturbances on an Arduino-based distribution channel, so that if there is a disturbance or disconnection in the distribution channel it can be quickly detected. Where the system works with the Arduino Mega2560 control and is monitored using Android via the Blynk programming. The system begins by activating the device and is continued by connecting (pairing) the ESP8266 with Android Wifi, with the name test wifi and password 88888888, if it is connected, the user can open the Blynk application on a Smartphone. The ACS712 sensor on the device is used to detect current and the ZMPT101B sensor is used to detect voltage and the results of the reading will be processed by Arduino Mega2560. Then if there is a short circuit / disconnection of electricity in the power line, the notification will enter the android via the Blynk application. The process of sending data from Arduino is carried out by ESP8266 which has been configured with Arduino. So that monitoring of disturbance status can be seen on Android